Las revistas políticas argentinas. Desde el peronismo a la dictadura (1973- 1983) - Saborido, Mercedes (Revista de Historia Social y de las Mentalidades, 2022)
This book studies the editorial position of the most prominent political magazines in Argentina of the seventies and first years of the eighties in the face of key events. The selected publications cover a wide ideological and journalistic range